Pituitary size alteration and adverse effects of radiation therapy performed in 9 dogs with pituitary-dependent hypercortisolism. (June 2018) - Sawada, Harumi; Mori, Akihiro; Lee, Peter; Sugihara, Shiho; Oda, Hitomi; Sako, Toshinori
Abstract: The purpose of this study was to determine the therapeutic and/or adverse effects of radiation therapy (RT) against pituitary tumors in dogs with pituitary-dependent hypercortisolism, as monitored by frequent post-RT detailed MRI examinations, clinical signs, and changes in hormone concentrations. Nine dogs with an adrenocorticotropic hormone (ACTH)-secreting pituitary mass diagnosed by magnetic resonance imaging (MRI) underwent RT for 4 weeks (total of 48 Gy in 4-Gy fractions). Pituitary height/brain area (P/B) value, clinical signs, basal plasma ACTH concentrations, serum cortisol concentrations (pre- and post-ACTH stimulation test) and adverse effects of RT were evaluated before and post-RT. The P/B value was significantly lower in all nine dogs post-RT. One dog lacking any neurological signs demonstrated no change in clinical signs pre and post-RT. Out of 8 dogs which exhibited neurological signs pre-RT, half of them demonstrated complete resolution of their signs, whereas the other half showed transient resolution. In all animals with recurrence of neurological signs, pituitary tumor regrowth was not observed; however, MRI revealed moderate to severe pituitary hemorrhage. Late adverse effect (bilateral otitis media) was observed in three of nine dogs post-RT. RT did not induce any significant changes in the dogs' basal plasma ACTH concentration and pre- and post-ACTH serum cortisol concentrations. In conclusion, RT is effective to reduce pituitary size and the mass effect, but does not appear to affect blood hormone concentrations, necessitating additional medical treatment against hypercortisolism. Periodic MRI imaging post-RT enables early detection of adverse effects of RT. Highlights: Radiation therapy was performed on 9 dogs with pituitary-dependent hypercortisolism. The pituitary height/brain area (P/B) value decreased after radiation therapy. No significant changes in hormone concentrations occurred after radiation therapy. Additional medical treatments are needed against hypercortisolism after radiation therapy. Monitoring by MRI enables early detection of complication after radiation therapy.